SEXUAL BEHAVIOURS AND HUMAN PAPILLOMAVIRUS GENOTYPING AMONG BOSNIAN WOMEN - Sabina Mahmutovic-Vranic (Peytchinski Publishing, 2020)
Purpose: Youth represents the most vulnerable population, mainly due to their lifestyle derived from risky sexual behaviours. The aim of the study was to identify specific HPV genotypes correlating with cervical smear cytologic abnormalities, well as sociodemographic/behavioural characteristics and history of sexually transmitted diseases in Bosnian women age up to 30 years. Methods: The longitudinal study was performed at the Department of Microbiology School of Medicine University of Sarajevo and Institute for Public Health dr. Andrija Stampar, Zagreb, Croatia from June 2017 to January 2018. Thirty (30) cervical smears were taken from tested females were screened using COBAS assay for HPV DNA testing. Routine Pap screening was performed in the Public Institution Department for Health Care of Women and Maternity of Sarajevo Canton. A self-administered questionnaire was applied. Results: A total of 30 sexually active women with abnormal cytological reports were enrolled in the study. The mean age was 26 IQR (20.75, 29.0) year. The overall prevalence of HR HPV was 66.7 %. Women age of ≤25 years had a positive association with positive results of HPV testing, OR=1.91. Consummation of alcohol, cigarettes had a strong positive association with positive HPV testing. Conclusions: The data obtained from this study indicate that HPV 16 is the most common HPV type found in the cervical specimens among young Bosnian women, followed by HPV 18. HPV DNA testing using as a screening test should be considered in the development of cervical cancer prevention programs in Bosnia and Herzegovina.